Letter to the Editor regarding the Revisional Surgery After One Anastomosis/Minigastric Bypass: an Italian Multi-institutional Survey. Obes Surg. 2022 Feb;32(2):256-265. doi: 10.1007/s11695-021-05779-y - Eduardo Lemos de Souza Bastos (Obesity Surgery, 2022)
INTRODUCTION: This study aims to evaluate clinical and economic outcomes of using different ultrasonic energy devices in patients undergoing sleeve gastrectomy (SG). METHODS: The patient cohort was extracted from PINC AI™ Healthcare Data 2019-2023, including individuals aged ≥ 18 who underwent primary elective gastric sleeve procedures using either corded (CD) or cordless (CL) ultrasonic devices (UD). Two analysis groups were evaluated: total SG regardless of the - stapler brand used in the operation (Cohort I), and UD used with an identifiable same-brand stapler in the operation (Cohort II). A propensity score matching (PSM) method with a caliper of 0.2 and 1:1 nearest-neighbor matching was performed for patients who used CD and CL. We applied multivariable generalized linear model (GLM) analyses for sensitivity analyses. RESULTS: 24160 and 18906 patients were included for cohorts I (82.3% CD and 17.7% CL; 4268 PSM paired) and II (81.7% CD and 18.3% CL; 3282 PSM paired), respectively. CD had higher operating-room time (minutes) than CL in both Cohort I (mean difference: 27 (95% confidence interval (CI): (24, 29), p < 0.001) and II (27 (24, 30), p < 0.001). There is no difference in incidence rates of blood transfusion, bleeding, and 30-day readmission, and total inpatient cost and length of stay between CD and CL. The sensitivity analyses showed similar results. CONCLUSIONS: The study shows that CL had similar clinical and economic outcomes to CD, and CL was more efficient in patients treated with sleeve gastrectomy. KEY POINTS: • Cordless ultrasonic devices were more efficient when used in sleeve gastrectomy. • Outcomes of sleeve gastrectomy used cordless/corded ultrasonic device were similar. • Resource use of cordless/corded ultrasonic device was similar in sleeve gastrectomy.